Small PLTS Off Grid 240 WP on Residential House Rooftop - Eko Yudiyanto; Lisa Agustriyana; Nila Alia; Puspitasari, Etik (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
Small PLTS on residential rooftops are now being widely applied. It can contribute to using alternative energy to support government programs to save electricity costs. It can also be used as backup electricity when PLN power outage. The purpose of this research is to be able to calculate the use of electric power in residential homes, design and make small PLTS off grid 240 WP from the use of electric power, calculate BEP when the payback time of the total investment in the procurement of small PLTS 240 WP with DC and AC systems. 240 WP power on the rooftop of a residential house is carried out for a load of 8 lights AC with 6 watts and one fan. This research showed that the total daily electric power usage was 0.55 kWh/day or 16.5 kWh/month. The design of 240 WP PLTS on the rooftop of a residential house according to the total household electricity needs of 550 watts/day requires core equipment such as two solar panels (120 WP), one battery (12 V 100 Ah), Inverter (12 V to 220 V) = 1000 Watt or 1 kWh as much as one piece, SCC = 20 A as much as one piece. The results of making 240 WP PLTS on the rooftop of a residential house accorded to the total electrical power needs of the household. Break Even Point on this application of 240WP solar power PLTS on residential rooftops with 1300 V power will return capital in 19.5 years. Where the total investment cost of procuring 240 WP PLTS is Rp. 5,558,000, and the cost of electricity per month from the above load is Rp. 23,850 / month or Rp. 286,200 / year.